Detecting the relativistic bispectrum in 21cm intensity maps. Issue 6 (22nd June 2021) - Jolicoeur, Sheean; Maartens, Roy; De Weerd, Eline M.; Umeh, Obinna; Clarkson, Chris; Camera, Stefano
Abstract: We investigate the detectability of leading-order relativistic effects in the bispectrum of future 21cm intensity mapping surveys. The relativistic signal arises from Doppler and other line-of-sight effects in redshift space. In the power spectrum of a single tracer, these effects are suppressed by a factor ℋ 2 /k 2 . By contrast, in the bispectrum the relativistic signal couples to short-scale modes, leading to an imaginary contribution that scales as ℋ/k, thus increasing the possibility of detection. Previous work has shown that this relativistic signal is detectable in a Stage IV Hα galaxy survey. We show that the signal is also detectable by next-generation 21cm intensity maps, but typically with a lower signal-to-noise, due to foreground and telescope beam effects.